Investigation on the elements of Malay landscape design - Ahmad, Abdullah Sani; Abu Bakar, Jamil; Ibrahim, Fawazul Khair (UTM, 2006)
This Malay landscape character research cover landscape architecture with the foundation of functions and Malay culture. Two main components that lead to developing Malay landscape architecture are plants and landscape furniture. These components consist of culture and artistic values that portray the Malay symbolism. Values on belief, world of thought and the culture had been the base of Malay cosmology. These values are indirectly defined by the design, art, composition, symbol and function. These elements also consist of indirect values and symbolism that can be ascertain through the perception of meaning that are meant to be delivered either in the aspect of culture or function. The qualitative and quantitative methods had been used to determine the elements and components of the Malay landscape either in physical or metaphysical form. The qualitative method focused on the symbolism in the Malay landscape through inventories and interviews with the respondent. Quantitatively, the research evaluate the statistic of landscape components that indicate the typology, function and the overall resemblance. The research data also define the existence of Malay landscape architecture from these values. Lastly, the characteristic of Malay landscape that had been identified will be used for the guideline of Malay landscape design that are relevant in the present environment.